2018
DOI: 10.1109/toh.2018.2844186
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Ultrasonic Switches Involves Large Discontinuity of the Mechanical Impedance

Abstract: The distinct tactile feedback provided by mechanical keyboards notifies users that their actions have been successfully recorded. The presence of these subtle yet informative tactile cues is one of the reasons why mechanical keyboards are still preferred to their virtual counterparts. An artificial sensation of pressing a mechanical switch can be produced by varying the coefficient of friction as the user is pressing down on a glass surface using ultrasonic vibration. We examined the factors involved in produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Therefore, to obtain a same perceptual intensity of a tactile stimuli, the vibration amplitude should be adapted according to the scanning speed and pressing force, which can be measured with sensors, but also to the biomechanical properties of the finger pad, which change from one user to the other. In [8], the measured acoustical impedance is correlated to the perception of simulated keyclick, since this measure is directly correlated to the biomechanical properties of the finger pad. The authors propose to use this *This work has been carried out within the framework of the Mint Project of IRCICA (Service and Research unit from CNRS) 1,2 The authors are with Univ.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to obtain a same perceptual intensity of a tactile stimuli, the vibration amplitude should be adapted according to the scanning speed and pressing force, which can be measured with sensors, but also to the biomechanical properties of the finger pad, which change from one user to the other. In [8], the measured acoustical impedance is correlated to the perception of simulated keyclick, since this measure is directly correlated to the biomechanical properties of the finger pad. The authors propose to use this *This work has been carried out within the framework of the Mint Project of IRCICA (Service and Research unit from CNRS) 1,2 The authors are with Univ.…”
Section: Introductionmentioning
confidence: 99%
“…This metric is used to control the force applied by robotic grippers to soft and fragile objects (19)(20)(21). In haptic rendering, it is possible to produce tactile sensations by releasing the accumulated stress using ultrasonic friction modulation (22). However, the perception of the frictional strength with a single normal motion is not as salient.…”
mentioning
confidence: 99%
“…A higher finger velocity was found to increase the intensity of the perception [32]. Interestingly, it has been shown that transient changes in friction could also be perceived with static touch [33] to recreate the illusion of pressing a button. Other studies have shown that the perception of two superimposed friction modulated sinusoidal gratings presents masking effects [34], [35].…”
Section: Perception Of Friction Modulationmentioning
confidence: 92%